Pengaruh Mol Nasi Basi Terhadap Pertumbuhan Dan Produksi Bawang Merah (Allium Ascalonicum L.) - Edwar Bahar (PUCUK : Jurnal Ilmu Tanaman, 2025)
Shallots (Allium ascallonicum L.) are one of the superior vegetable commodities that have long been cultivated intensively by farmers. Domestic production of shallots has not been able to meet the needs of shallot consumers because the farming system is less than optimal, the condition of the land is not good and optimal, and the use of seed planting materials that have decreased quality. One effort that can be made to overcome the current problems of shallot cultivation is to increase soil fertility by improving the physical, chemical and biological properties of the soil and adding optimal organic and inorganic materials. This can be done by using stale rice MOL so that it is expected to be able to improve the physical and chemical properties of the soil, loosen the soil and make it easier for plant roots to absorb nutrients in the soil. The purpose of the study was to determine the effect of stale rice MOL on increasing the growth and production of shallots, and to obtain the dose of stale rice MOL in increasing the growth and production of shallots. This study was conducted using a Completely Randomized Design (CRD) with 5 treatments and 3 replications so that 15 experimental units were obtained, each experimental unit consisting of 6 plants where there were 3 sample plants. The results of the analysis showed that the provision of MOL concentration of stale rice and without the provision of MOL of stale rice showed different results on the weight of dry tubers, the weight of wet tubers, the number of leaves, the number of shoots, the height of the plant and the loss of tuber weight.